Tongass odyssey: seeing the forest ecosystem through the politics of trees: a biologist's memoir - Schoen, John, author; University of Alaska Press, publisher (Colorado State University. Libraries, 2020)
John Schoen's Tongass Odyssey is both a memoir and a scientific manuscript. As a memoir it offers authorial stories related to Schoen's dealings in the Tongass National Forest; as a science-based manuscript it addresses the ecological and political history of the past 50 years of the Tongass. It also addresses the responsibility of conservation practitioners regarding the consequences of public lands and water management.--Provided by publisher.
The making of a biologist (1947-1976) -- Tongass field research (Alaska Department of Fish & Game 1977-96) -- Tongass rainforest : saving all the parts (Audubon 1997-2011; retirement 11-19) -- Personal reflections.
Keywords: Ecologists -- United States -- Biography; Forest ecology -- Research -- Alaska -- Tongass National Forest; Forest conservation -- Alaska -- Tongass National Forest -- History; Environmental protection -- Alaska -- Tongass National Forest -- History; Schoen, John W.; Tongass National Forest (Alaska) -- History; Alaska. ǂb Department of Fish and Game -- Officials and employees -- Biography; Tongass National Forest (Alaska) -- Environmental conditions; Audubon Alaska -- Officials and employees -- Biography